Gambaran proses penerimaan saudara kandung penyandang disabilitas intelektual - Cindy, Stephanie; Sudarji, Shanty (Konsorsium Psikologi Ilmiah Nusantara, 2018)
Intellectual disability is a developmental disorder which is characterized by deficiency in the mental processing. This deficit leads to the inability in adaptation, which makes individuals unable to fulfill their own living standard and social responsibilities in many aspects of life. Siblings play an important role in the development of children diagnosed with intellectual disability. The existence of children with intellectual disability could affect their sibling in positive or negative way. The purpose of this research was to illustrate the siblings’ acceptance regarding their siblings whom were diagnosed with intellectual disability, the factors that affect their acceptance, and the process of how the acceptance formed. This qualitative study used phenomenological approach by doing observation and interview to the responsdents. This research was conducted on five adolescents (15- 18 years old) whose sibling diagnosed with intellectual disability. The result of this research showed that three subjects have reached the acceptance phase, while two other subjects have not reached acceptance phase. This research also indicates good family communication, proper knowledge, and positive perception regarding intellectual disability as several factors that affect three successful subjects to reach the acceptance phase.